Hierarchical Assembly of Tough Bioelastomeric Egg Capsules is Mediated by a Bundling Protein - Loke, Jun Jie (2017)
Marine snail egg capsules are shock-absorbing bioelastomers made from precursor “egg case proteins” (ECPs) that initially lack long-range order. During capsule formation, these proteins self-assemble into coiled-coil filaments that subsequently align into microscopic layers, a multiscale process which is crucial to the capsules’ shock-absorbing properties. In this study, we show that the self-assembly of ECPs into their functional capsule material is mediated by a bundling protein that facilitates the aggregation of coiled-coil building blocks and their gelation into a prefinal capsule prior to final stabilization. This low molecular weight bundling protein, termed Pugilina cochlidium Bundling Protein (PcBP), led to gelation of native extracts from gravid snails, whereas crude extracts lacking PcBP did not gelate and remained as a protein solution. Refolding and reconcentration of recombinant PcBP induced bundling and aggregation of ECPs, as evidenced by ECPs oligomerization. We propose that the secretion of PcBP in vivo is a time-specific event during the embryo encapsulation process prior to cross-linking in the ventral pedal gland (VPG). Using molecular dynamics (MD) simulations, we further propose plausible disulfide binding sites stabilizing two PcBP monomers, as well as a polarized surface charge distribution, which we suggest plays an important role in the bundling mechanism. Overall, this study shows that controlled bundling is a key step during the extra-cellular self-assembly of egg capsules, which has previously been overlooked.